A Rapid Method of Identification of Garnet in Beach Sands Using Laser-Induced Breakdown Spectroscopy (Journal of Bangladesh Academy of Sciences, 2020)
In this work, Laser Induced Breakdown Spectroscopy (LIBS) has been used for investigating the presence of heavy mineral garnet (X3Y2(SiO4)3, where the X represent either of Ca2+ , Mg2+, Fe2+, Mn2+ and the Y site contain either of Fe3+, Cr2+, Al3+ ) in beach sand samples collected from Sitakunda, Bangladesh. To achieve the goal, in the first attempt, a comprehensive spectral profiling of the laboratory grade garnet was done and the identified emission lines were employed as the reference lines for discovering the presence of the elements of garnet in the LIBS spectra of different sand samples and an arbitrary soil sample. The average intensity ratio for these reference lines of Mg, Al, Fe, Mn, Ca, estimated in different sand samples and the isolated garnet sample, is found to be about 60 % (against the average intensity ratio of about 20 % estimated for general soil sample and garnet), substantiating the presence of garnet in sand with significant concentration. Therefore, LIBS can be used as a useful alternative experimental tool for predicting the presence of minerals in the sand samples and for the exploration of new geological site in Bangladesh.Journal of Bangladesh Academy of Sciences, Vol. 43, No. 2, 149-157, 2019